2010
DOI: 10.1111/j.1745-4514.2010.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biosurfactants From Natural Resources

Abstract: Role of biosurfactants has shown renewed interest; hence, search for readily available natural resources of these materials is continuing. Chicken viscera and bahera oil were used as natural sources of oleic acid and its methyl ester, respectively, for the preparation of biosurfactants. Enzymatic esterification and transesterification of oleic acid were performed with sorbitol, fructose and ascorbic acid using Candida antarctica lipase, and their isolated yields were compared. Oleyl esters of sorbitol, fructos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
(44 reference statements)
0
11
0
1
Order By: Relevance
“…These FFA lipids contain saturated as well as unsaturated FA, in which palmitic and stearic acid are the main saturated FA present in both chicken and fish viscera. Based on previous reports [17,19], acetone is the most suitable and commonly used solvent for separation of saturated and unsaturated FA. In this study the same solvent was also used to remove saturated FA by adopting the low-temperature crystallization method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These FFA lipids contain saturated as well as unsaturated FA, in which palmitic and stearic acid are the main saturated FA present in both chicken and fish viscera. Based on previous reports [17,19], acetone is the most suitable and commonly used solvent for separation of saturated and unsaturated FA. In this study the same solvent was also used to remove saturated FA by adopting the low-temperature crystallization method.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have shown that this processing waste could be used as an animal feed [12][13][14] and also for the production of oil [15] or biodiesel [16]. Although reports are available on the FA profile of chicken viscera [17] and hilsa fish oil [18], isolation of PUFA from these materials is as yet unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar‐based fatty acid esters are non‐ionic, biodegradable, odorless, non‐irritating, non‐toxic surfactants that possess important emulsifying properties. These esters have application in innumerous areas including pharmaceuticals, cosmetics, detergents, and food industry, having properties that could be explored, such as emulsion forming and stabilization, antiadhesive and antimicrobial activities 1–4.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to the synthesis of sugar esters derivatives is the enzymatic synthesis, which avoids the problems generated in chemical synthesis 1. Enzymatic synthesis in organic media allows one to obtain higher selectivity and pure products because of enzyme specificity 5–7.…”
Section: Introductionmentioning
confidence: 99%
“…In India, the fruit extract is generally used against myocardial necrosis or hypoglycemic activity (Kar et al 2003). Moreover, extraction of oil from Bahera seed kernels has been reported (Bera et al 2007;Patil et al 2010), but production of gallic acid from the tannin present in the seed coat that left after removing the kernels is yet unexplored.…”
Section: Introductionmentioning
confidence: 99%